2022
DOI: 10.1126/science.abj3068
|View full text |Cite
|
Sign up to set email alerts
|

Demographic implications of lead poisoning for eagles across North America

Abstract: Lead poisoning occurs worldwide in populations of predatory birds, but exposure rates and population impacts are known only from regional studies. We evaluated the lead exposure of 1210 bald and golden eagles from 38 US states across North America, including 620 live eagles. We detected unexpectedly high frequencies of lead poisoning of eagles, both chronic (46 to 47% of bald and golden eagles, as measured in bone) and acute (27 to 33% of bald eagles and 7 to 35% of golden eagles, as measured in liver, blood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Yet carrion can have detrimental effects on scavengers and other species. If hunters shoot lead bullets, the carrion may expose scavengers to lead (Haig et al 2014, Stokke et al 2017, Slabe et al 2022). Food subsidies can maintain higher carnivore numbers, thus increasing predation on vulnerable species (Oro et al 2013, Tobajas et al 2021).…”
mentioning
confidence: 99%
“…Yet carrion can have detrimental effects on scavengers and other species. If hunters shoot lead bullets, the carrion may expose scavengers to lead (Haig et al 2014, Stokke et al 2017, Slabe et al 2022). Food subsidies can maintain higher carnivore numbers, thus increasing predation on vulnerable species (Oro et al 2013, Tobajas et al 2021).…”
mentioning
confidence: 99%
“…Among raptors preying on stubble quail, the wedge-tailed eagle ( Aquila audax ) is known to accumulate harmful amounts of lead in bone as a result of the ingestion of lead-based ammunition [ 57 59 ]. Given that this eagle species is a K-strategist, with a high adult survival rate and a low productivity [ 59 , 60 ], lead poisoning likely exerts adverse effects on it at the population level, as observed in other long-lived apex avian predators with similar life history traits [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many species of predatory and scavenging birds [ 6 , 7 ] and mammals [ 16 , 17 ] are affected across the world. Lead poisoning is estimated to kill millions of waterbirds every year [ 5 ] and suppress the populations of raptors across North America [ 18 , 19 ] and Europe [ 20 ] and thus is of substantial conservation significance.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lethal exposure can be widespread as a result of this process (Slabe et al . 2022) but equally concerning is the potential for sublethal effects resulting in chronic health degradation (Pay et al . 2021), as has been demonstrated for Golden Eagles ( Aquila chrysaetos ) in Europe (Ecke et al .…”
Section: Introductionmentioning
confidence: 99%
“…Avian, mammalian and reptilian scavengers feed extensively on discarded macropod tissues (Read & Wilson 2004). Acute lethal exposure can be widespread as a result of this process (Slabe et al 2022) but equally concerning is the potential for sublethal effects resulting in chronic health degradation (Pay et al 2021), as has been demonstrated for Golden Eagles (Aquila chrysaetos) in Europe (Ecke et al 2017;Singh et al 2021). Avian species known to be at-risk throughout Australia include Wedge-Tailed Eagles (A. audax) (Lohr et al 2020;Hampton et al 2021;Pay et al 2021; Figure 2).…”
mentioning
confidence: 99%